JABOTICABAL EM NOTICIAS: ORGÃO INFORMATIVO DO CAMPUS DE JABOTICABAL – UNESP - Agricultura, Revista (REVISTA DE AGRICULTURA, 2015)
JABOTICABAL EM NOTICIAS: ORGÃO INFORMATIVO DO CAMPUS DE JABOTICABAL – UNESP